Multi-Objective Optimization Path of Countermeasure Research on High-Quality and Balanced Development of Compulsory Education in Hebei Province in the Context of Digital Era - Zhang, Suwei; Yu, Hongxia; Yang, Xiangxiang; Li, Chao; Liu, Zhihua; Liang, Xiaohui (Applied mathematics and nonlinear sciences, 2025)
This paper analyzes the current situation and constraints in the allocation of resources for compulsory education in urban and rural areas of Hebei Province. It establishes a system for assessing the balanced development of the quality of compulsory education. And on the basis of this system, the overall and inter-school high-quality and balanced development of compulsory education in Hebei Province is measured through the object-element analysis method. The allocation of educational resources in districts and counties of Hebei Province is optimized through the Pareto multi-objective optimization algorithm. It is known from the study that the investment in education in Hebei Province has been increasing, growing to 529,846,700,000 yuan in 2023, and the development level of education has been increasing, with similar conditions in urban and rural schooling. However, there are still problems such as an imbalance in the structure of academic subjects and excessive inter-school differences. There are also 27.3% of schools whose overall evaluation of education quality is lower than the average level of education quality. The optimization strategy for the allocation of educational resources in the compulsory education stage proposed in this paper is of great significance in promoting the progress of balanced development of education.